Creatures of the Namib desert - Saxon, David; Hughes, David; National Geographic society, Washington, D. C. WQED (Television station : Pittsburg, Pa.). ([Washington, D. C.] National Geographic Video, 1977)
Narrated by Burgess meredith, this program takes a look at the vast wilderness of the Namib Desert and shoes how creatures adapt to the environment.
Narrated by Burgess Meredith; Narration written by Mirriam Birch; Edited by David Saxon.
Keywords: Namib Desert (Namibia).; Desert ecology -- Namibia